2006
DOI: 10.1111/j.1557-9263.2006.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Nest box orientation affects internal temperature and nest site selection by Tree Swallows

Abstract: Orientation of nests can influence nest microclimate, particularly temperature. However, few investigators have examined orientation preference and microclimate simultaneously. We examined the possible correlation between entrance orientation of artificial nest boxes used by Tree Swallows (Tachycineta bicolor) and the internal temperature of boxes. Tree Swallows showed a preference for east‐ and south‐facing boxes, but only during the first half of the breeding season (before 1 June). During the second half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 26 publications
7
109
0
3
Order By: Relevance
“…Similar shifts in preferences for sleeping site characteristics linked to temperature changes have been reported for birds (e.g. Ardia et al 2006;Velky et al 2010). It is well documented that tree holes can buffer against temperature fluctuations (Schmid 1998;Sedgeley 2001;Willis & Brigham 2007;Isaac et al 2008) and the change in sleeping site usage that we observed may thus indicate the lower thermoregulatory constraints experienced by the females during the wet season.…”
Section: Thermoregulatory Demands and Sleeping Sitessupporting
confidence: 75%
“…Similar shifts in preferences for sleeping site characteristics linked to temperature changes have been reported for birds (e.g. Ardia et al 2006;Velky et al 2010). It is well documented that tree holes can buffer against temperature fluctuations (Schmid 1998;Sedgeley 2001;Willis & Brigham 2007;Isaac et al 2008) and the change in sleeping site usage that we observed may thus indicate the lower thermoregulatory constraints experienced by the females during the wet season.…”
Section: Thermoregulatory Demands and Sleeping Sitessupporting
confidence: 75%
“…This daily pattern of heating and cooling could provide ecophysiological benefits to nocturnal mammals using cool chainsaw hollows (relative to external ambient conditions) during warm summer days by decreasing the amount of evaporative heat-loss required to maintain constant body temperature [39,40]. It could also benefit diurnal hollow-nesting birds using warm (compared to ambient) chainsaw hollows at night by decreasing the amount of metabolic heat production required to maintain core body temperature [41,84]. In contrast, glider and bat boxes had the opposite pattern of heating and cooling, being slightly colder than ambient at night and substantially hotter during the day.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, birds are able to influence nest microclimates by preferentially occupying nestboxes in relation to the orientation of their entrance hole which influences the exposure to cold winds (e.g., Ardia et al, 2006) and their construction material because woodcrete nestboxes are about 1.5 • C higher on average than wooden nestboxes (e.g., García-Navas et al, 2008). Studies show that whilst great tits avoided nestboxes orientated toward south-southwest, there was no such relationship in blue tits, although the orientation of nestboxes did not influence reproductive success in either species (Goodenough et al, 2008).…”
Section: Environmental Adjustmentmentioning
confidence: 99%